Análise da produção técnico-científica dos pesquisadores do Programa Nacional de Pesquisa de Caprinos, no período de 1977 a 1988 - Valois, Eliana Candeira (1990)
The technical and scientific paper production of the National Program on Goat Research is quantitatively analysed for the period of 1977 to 1988. The analysis was made in two levels: the individual paper production and for the institutions dealing with goat, considering institutional research programs. All the research units were studies in relation to documentation produced divided by country region, state of Brazilian federation, language of paper production, year of document generation and research specification. The individual paper production by researchers was analysed through Lotka´s law the Elitism law was applied. It was verified a great diversity of documents due the institutional support, researchers productivity and dissemination factors, being distinguished the research front reproduction and management. The results indicated that author productivity is kept in a small amount according to bibliometrics laws as well as collaboration among authors. There is no conformity of Lotks/Price lawin the field. In the elite paper production study, twenty authors were analysed. It has shown dinamic relations in the institutions and among them. A sociogram of these relations was prepared.